Low Serum Calcium and Magnesium Levels and Rupture of Intracranial Aneurysms - Can, Anil (Stroke, 2018)
BACKGROUND AND PURPOSE: Both low serum calcium and magnesium levels have been associated with the extent of bleeding in patients with intracerebral hemorrhage suggesting hypocalcemia and hypomagnesemia induced coagulopathy as a possible underlying mechanism. We hypothesized that serum albumin-corrected total calcium and magnesium levels are associated with ruptured intracranial aneurysms. METHODS: The medical records of 4,701 patients, including 1,201 prospective patients, diagnosed at the Brigham and Women’s Hospital and Massachusetts General Hospital between 1990 and 2016 were reviewed and analyzed. 1,275 patients had available serum calcium, magnesium, and albumin values within 1 day of diagnosis. Individuals were divided into cases with ruptured aneurysms and controls with unruptured aneurysms. Univariable and multivariable logistic regression analyses were performed to determine the association between serum albumin-corrected total calcium and magnesium levels, and ruptured aneurysms. RESULTS: In multivariable analysis both albumin-corrected calcium (OR 0.33, 95% CI 0.27–0.40) and magnesium (OR 0.40, 95% CI 0.28–0.55) were significantly and inversely associated with ruptured intracranial aneurysms. CONCLUSIONS: In this large case-control study, hypocalcemia and hypomagnesemia at diagnosis were significantly associated with ruptured aneurysms. Impaired hemostasis due to hypocalcemia and hypomagnesemia may explain this association.